Argument coding in the experiential predicate tǝmʃʌ kǝrdǝn ‘to look’ in Garrusi Kurdish - Mohammad Dabir-Moghaddam; Masoumeh Zarei (زبان پژوهی)
tǝmʃʌ kǝrdǝn ‘to look’ is an experiential predicate in Garrusi Kurdish whose arguments and event structure are represented as a coverb complex predicate. The present study explores how arguments are encoded in the predicate-argument construction of tǝmʃʌ kǝrdǝn based on Croft’s typological perspective (2022). It investigates the strategies employed by this verbal event to express its participants’ roles, which grammatical and semantic functions are hosted by its components, and how its event structure is represented with respect to its argument structure. For this purpose, a fieldwork was conducted and 30 native speakers of Garrusi Kurdish were interviewed. Wallace Chafe’s The Pear Story film was used as a catalyst for data collection, and Kurdish narratives were recorded. A total of 88 tokens of tǝmʃʌ kǝrdǝn, extracted from our discursive corpus, were analyzed to study argument coding strategies. The findings revealed that this experiential complex predicate, exhibits variation in the participants’ argument coding and the type of the event it expresses. It basically used experiencer-oriented strategy, encoding the experiencer as a subject argument phrase. However, the stimulus showed variation in coding strategies, being expressed as an object argument phrase, as an oblique argument phrase, or as a complement clause. Of the 88 tokens of tǝmʃʌ kǝrdǝn, only 16 instances employed subject-object argument structure. The most tokenized coding strategy was subject-oblique argument coding with a locative/goal stimulus. Additionally, this complex predicate was observed to function as a subevent in serial verb construction. It could also express a different event structure.